THE ROLE OF UZBEK FOLKLORE IN THE EDUCATION OF MODERN YOUTH - Qulmatov Primqul Meliqo’zievich; Turatov Shuxrat Baxromovich (Journals Park Publishing, 2022)
The article analyzes the socio-philosophical analysis of the need for folklore, which today is of great importance in the prevention of spiritual threats and the upbringing of a harmoniously developed generation. attention is also paid to the issue of the factors influencing the youth of folk oral art.
Keywords: spiritual threat; folklore; reforms of Uzbekistan